Governed Through Ghost Jurisdictions: Municipal Law, Inner Suburbs and Rooming Houses. (7th February 2017) - Freeman, Lisa
Abstract: This article examines the legal geography of municipal bylaws regulating rooming houses in the City of Toronto. Using a legal geography analysis of Toronto's rooming house licensing bylaw, I argue that this bylaw is a ghost jurisdiction that designates part of the city as illegal and has implications for governance of the inner suburbs. In so doing, I push the debate on legal geography forward by suggesting that we, as urban scholars, take the temporal seriously in our analysis of space. Drawing from semi‐structured interviews, archival data and participant observation, I analyse seemingly mundane legal mechanisms through the case study of suburban rooming houses. Overall, in this article I make three contributions. First, I demonstrate how a temporal analysis is important to legal geography inquiries of uneven regulation and spaces of poverty. Second, I suggest that studies of legal governance are integral for redefining suburban governance amidst socio‐economic decline in the inner suburbs. Third, I argue that studying urban legal mechanisms in the suburbs is essential for moving beyond downtown analytical frameworks and is needed to address how low‐income suburban tenants, a large majority of whom are racialized newcomers, are unevenly regulated and unfairly governed by local government.